Key decision factors of professional stakeholders (architects, engineers, constructors) when deciding for sustainable construction - Primožič, Lea; Kutnar, Andreja (Frontiers in Built Environment, 2024)
The built environment and the construction industry account for a significant share of global harmful emissions. Sustainable construction appears to be an effective strategy to achieve a more sustainable society, although it is still not used enough. It is crucial to understand what the main decision factors of those deciding about building practices are. Professional stakeholders such as architects, engineers, constructors, are the ones advising consumers and deciding about construction. An understanding about their decision factors is needed, in order to increase the implementation of sustainable construction. In this study we provide evidence about key decision factors of professional stakeholders in Slovenia when deciding for sustainable construction practices. By conducting an online survey (questionnaire) we identified and analyzed the main drivers and barriers of professionals when making decisions about sustainable construction solutions. With statistical analysis we found out that professional stakeholders included in the survey mostly already had previous experiences working with sustainable construction. They are familiar with sustainable construction concepts. The most important drivers were connected to the factor of occupant health, and the energy-efficiency of the buildings, while the biggest barrier in their decision making is related to higher cost of sustainable construction and lack of awareness. Professional stakeholders are concerned about climate change and their attitudes towards climate change are affecting their decision related to sustainable construction. Respondent provided many comments, clearly indicating that a simple definition of sustainable construction is needed, and more efforts should be done to raise awareness about sustainable construction. Results are contributing valuable information for professional stakeholders, policy makers and other important stakeholders in the construction ecosystem.